Public Response to Waste from The Rejeki Gangsar Slaughterhouse in Bulurejo - Riandika Adi Perdana; Ludfia Windyasmara (Jurnal Biologi Tropis, 2026)
Slaughterhouse waste is a residual material produced from the process of slaughtering animals in slaughterhouse facilities. This waste can include organic materials, such as blood, offal, bones and leftover meat, which can become a source of environmental pollution if not managed properly. Effective management of RPH waste crucial for reducing environmental impacts and maintaning public health. This study aims to determine public perceptions regarding the impact of slaughterhouse waste on environmental health and public welfare regarding waste around slaughterhouses. The method used in this study is a qualitative method by means of direct observation in the field by conducting a survey at the Rejeki Gangsar Slaughterhouse (RPH) and distributing questionnaires to the community for 30 sample respondents around the RPH which are divided into 2 radii, namely with a distance of less than 100 m and more than 100 m with 15 respondents each. The results of statistical analysis show that the community's response to air quality, the presence of animals that disturb water quality, the impact on health, and the socio-economic impact in this study, the different distances between houses affect the data to be non-significant. In this study, the distance between people's houses is different, so that people's responses are not uniform and are difficult to detect as significant in data analysis.